Structural performance of fish market in Bogura district, Bangladesh (Research in Agriculture Livestock and Fisheries, 2018)
One of the most important blossom trades in the economy of Bangladesh is fish marketing. To understand the current practices of fish market and marketing systems in Bogura district of Bangladesh, an investigation was conducted based on existing marketing system and economic features of marketing activities and inefficiencies. Fish marketing is almost exclusively maintained by the private sector and large number of intermediaries such as local traders, agents/suppliers, and retailers are involved in the distribution process of fish marketing. Data were collected from 45 fish traders through questionnaire interviews and participatory rural approach methods during December 2011 to May 2012 from three different fish markets named as Fateh Ali Fish Market, Godarpara Fish market and Khandar Fish market of Bogura district. The daily supply of fish in Fateh Ali Fish market, Godarpara Fish market and Khandar Fish market were estimated at 6.75 tons, 0.765 tons and 0.495 tons, respectively. Present supply and requirement of the fish showed a wide gap and virtually most of the fish (85%) is imported from outside where the local supply of fish is only 15%. There is a high consumer preference for Indian major carps i.e. rohu, catal, mrigal and exotic carps silver carp, grass and common carp, tilapia, pangas etc. The price of fish depends on market structure, species, quality, size, weight and season that’s why a well-systematized marketing setup is crucial for reasonable price for fishes. The study revealed that almost all traders in three markets made a considerable amount of profit and broadly improved their food consumption facilities, standards of living, purchasing power, choice and ability as an economic sector. However concerns arise about the sustainable marketing system due to higher transport costs, poor transport facilities, inadequate supply of ice, lack of money for business, and poor institutional support. It is an urgent issue to establish ice factory, improvement of transport facilities, provision of governmental, institutional and banking assistance, introduction of fish quality control measures and training of fish market operators for improved their marketing system. Therefore, the present study emphasizes the fundamental marketing system, market flow of fish, availability of fish in these three markets, and market related constraints in Bogura district, Bangladesh.Res. Agric., Livest. Fish.5(3): 399-410, December 2018